VIRAL HEPATITIS B AND C AS COMORBIDITY IN RHEUMATIC DISEASES: ANALYSIS OF THE DATA OF THE V.A. NASONOVA RESEARCH INSTITUTE OF RHEUMATOLOGY CLINIC OVER 4 YEARS - A. E. Karateev; N. V. Gontarenko; A. V. Tsurgan; A. A. Abramkin; L. D. Vorobyeva; D. V. Bukhanova (Научно-практическая ревматология)
Hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is a serious problem that substantially hinders the treatment of patients with rheumatic diseases (RD) particular when there is a need for using cytotoxic and biological agents (BAs).Objective: to estimate the rate of HBV and HCV infection in RD patients followed up at the V.A. Nasonova Research Institute of Rheumatology Clinic in 2011 to 2014.Subjects and methods. All case histories of the RD patients hospitalized in the given period were analyzed. Infection with HBV and HCV was assessed from the presence of HBsAg and anti-HCV, respectively.Results and discussion. There were a total of 16,553 admissions to the V.A. Nasonova Research Institute of Rheumatology Clinic over 4 years. HBV and HCV were detected in 0.33 and 0.74%, respectively; their combination was found in 0.03% (a total of 1.1%) of the patients. About half of the patients took cytotoxic agents and glucocorticoids; 29.8% received BAs, mainly rituximab. Moderate and high chronic hepatitis activity was noted in 4.9% of the patients; liver cirrhosis was observed in 2.7%. Over the follow-up period, alanine aminotransferase and aspartate aminotransferase levels were not elevated in the vast majority of patients.Conclusion. HBV and HCV infection is often detected in patients with RD. The infected patients and persons with chronic viral hepatitis require careful follow-up and the decision whether to perform prophylactic antiviral therapy when using cytotoxic agents and BAs.